If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4y + 7)(4 + -1y) = 0 Reorder the terms: (7 + 4y)(4 + -1y) = 0 Multiply (7 + 4y) * (4 + -1y) (7(4 + -1y) + 4y * (4 + -1y)) = 0 ((4 * 7 + -1y * 7) + 4y * (4 + -1y)) = 0 ((28 + -7y) + 4y * (4 + -1y)) = 0 (28 + -7y + (4 * 4y + -1y * 4y)) = 0 (28 + -7y + (16y + -4y2)) = 0 Combine like terms: -7y + 16y = 9y (28 + 9y + -4y2) = 0 Solving 28 + 9y + -4y2 = 0 Solving for variable 'y'. Factor a trinomial. (4 + -1y)(7 + 4y) = 0Subproblem 1
Set the factor '(4 + -1y)' equal to zero and attempt to solve: Simplifying 4 + -1y = 0 Solving 4 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = 0 + -4 -1y = 0 + -4 Combine like terms: 0 + -4 = -4 -1y = -4 Divide each side by '-1'. y = 4 Simplifying y = 4Subproblem 2
Set the factor '(7 + 4y)' equal to zero and attempt to solve: Simplifying 7 + 4y = 0 Solving 7 + 4y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 4y = 0 + -7 4y = 0 + -7 Combine like terms: 0 + -7 = -7 4y = -7 Divide each side by '4'. y = -1.75 Simplifying y = -1.75Solution
y = {4, -1.75}
| q(z)=pz+b | | ln*(x-5)+ln*(x-8)=ln*28 | | x-1/5=3-(x-9)/2 | | (150-80/1-x)2x=0 | | 40-(5)x=8+x | | (5-3x)2x=0 | | (4g-2)*(4g-2)=4 | | 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 | | 7x^2+7x=9 | | cos7x=cosx/3 | | 11-4+(-1)*5= | | 9t+18-3t-15= | | y=2x^4-4x^2+15 | | 2(2x-1)-3(x+3)=x+1 | | 7y+8y-3x-4x= | | 2x-25+7x-75=7x-20 | | 7x-x^3=6 | | 9x+3y-6x+2y= | | 4w+10=-3(w-8) | | 25x+7x-4x-6x= | | Sinx=-.72 | | 2(d+6)=-2d-12 | | X+40+y=180 | | 2x+33=7x+3 | | 0.84xa=1 | | X^2-(1+3i)x-2+2i=0 | | 5+3(2a-5)-(a-6)= | | 5X+20y=345 | | 16x^2-96x+25y^2=256 | | 3x+20y=345 |